2006
DOI: 10.1016/j.jecp.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A heart rate analysis of developmental change in feedback processing and rule shifting from childhood to early adulthood

Abstract: Over the course of development, the ability to switch between different tasks on the basis of feedback cues increases profoundly, but the role of performance monitoring remains unclear. Heart rate indexes can provide critical information about how individuals monitor feedback cues indicating that performance should be adjusted. In this study, children of three age groups (8-10, 12-14, and 16-18 years) performed a rule change task in which sorting rules needed to be detected following positive or negative feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 56 publications
3
39
0
Order By: Relevance
“…This stronger reaction to external feedback in children as compared with adult age groups is assumed to be compensatory and related to a not-yet-fully-developed ability of children to exert internal motor control (Luna & Sweeney, 2004). In line with these considerations, the stronger reaction to feedback or cue stimuli in children has been attributed to a greater sensitivity to external as compared with internal feedback (Crone, Somsen, Zanolie, & van der Molen, 2006).…”
Section: Frn Decreases From Childhood To Early Adulthood and Old Agementioning
confidence: 92%
See 1 more Smart Citation
“…This stronger reaction to external feedback in children as compared with adult age groups is assumed to be compensatory and related to a not-yet-fully-developed ability of children to exert internal motor control (Luna & Sweeney, 2004). In line with these considerations, the stronger reaction to feedback or cue stimuli in children has been attributed to a greater sensitivity to external as compared with internal feedback (Crone, Somsen, Zanolie, & van der Molen, 2006).…”
Section: Frn Decreases From Childhood To Early Adulthood and Old Agementioning
confidence: 92%
“…Hence, the amplitude of the FRN differentiated less well between gains and losses in both children and older adults than in younger adults, although children showed the largest FRN response in general. This pattern suggests that despite the apparent stronger sensitivity to external feedback in children (Eppinger et al, 2009;Crone et al, 2006), the focus of the maturing outcome monitoring system does not yet yield a differentiated classification of the outcomes with respect to the individual task goals.…”
Section: Less Differentiated Gain/loss Distinction In Children and Olmentioning
confidence: 97%
“…During brain development, ACC shows a protracted maturation compared with more posterior brain regions (Casey, Tottenham, Liston, & Durston, 2005;Gogtay et al, 2004). Besides structural maturation, ACC also shows developmental change in functionality (e.g., for processing the informative value of feedback) until late adolescence (Crone, Zanolie, van Leijenhorst, Westenberg, & Rombouts, 2008;Crone, Somsen, Zanolie, & van der Molen, 2006). Together, these findings suggest an immaturity of brain structures and functions related to feedback processing in early childhood.…”
Section: Introductionmentioning
confidence: 92%
“…Developmental changes are observed in error monitoring until late adolescence, but different processes and associated neural circuitry may account for these differences. Thus, we examined feedback sensitivity in childhood (8-11 years), adolescence (14-15 years), and adulthood (18-25 years) using a child-friendly WCST-like feedback monitoring task (Crone, Somsen, Zanolie, & van der Molen, 2006) previously shown to be sensitive to process dissociability in the areas under study (Zanolie et al, 2008).…”
mentioning
confidence: 99%
“…However, we previously examined the development of feedback processing in children ages 8-10 and 11-12 and in adults in rule-learning paradigms using heart rate measures (Crone, Jennings, & van der Molen, 2004;Crone, Somsen, et al, 2006). These studies demonstrated that the presentation of negative feedback is associated with slowing of the subsequent heartbeat.…”
mentioning
confidence: 99%